Disposal of sewage sludge utilities on receipt of biofuels and biofertilizers - Дегтяр, Д.І.; Горлінський, О.В.; Карпенко, В.І. (Problems of Environmental Biotechnology, 2012)
In the process of anaerobic methane fermentation sludge municipal wastewater with animal waste (such as chicken and pig manure) in a ratio of 1:1 and 1:2, the volume of biogas formed is increased by 7-12% compared with the amount of biogas that received by digestion native pig manure, and 32-37% compared with the volume formed by biofuels in anaerobic digestion of chicken manure. Found that a mixture of sewage sludge and agricultural waste, generated in the process of anaerobic methane fermentation in making the soil in the laboratory helps to increase the speed of growth of cereals and legumes to 25-28% compared with native agriculture waste.